ヒガシ ナンキョク セールロンダーネ サンチ バルヒュン サン ト ソノ シュウヘン ノ ヌナタック ノ チケイ - 安仁屋, 政武; アニヤ, マサム; Aniya, Masamu (1989)
P(論文) 東南極セールロンダーネ山地の東端に位置するバルヒェン山とその周辺のヌナタックの地形について, バルヒェン山では現地調査と空中写真判読から作成した地形学図を, 主なヌナタックについては空中写真のステレオグラムを使って記載した。ヌナタックは周辺の大陸氷床よりも高くそびえ, その多くはおもに山岳氷河の侵食による起伏の大きい景観を呈しているが, バルヒェン山は大陸氷床の侵食による, 全体に起伏の緩い滑らかな地形である。またバルヒェン山の大部分は周辺の氷床より低く, その地形的な特徴と相まってセールロンダーネ山地では特異な地域となっている。 いくつかのヌナタックとバルヒェン山の東面は, 風化した物質が載る斜面と新鮮な基盤岩の斜面が上下にきれいに分かれており, 最近大陸氷床が数10m低下したことを示している。バルヒェン山では, 風化したerraticsやtillsが広域にわたって新鮮な基盤の上に堆積している。これは, 過去に周辺の大陸氷床から流れ下ってきた氷舌がこの付近で合流し, 消耗したからと考えられる。これらの風化基盤と風化堆積物の分布に基づき解氷過程が推定され, バルヒェン山の西面が標高が低いにもかかわらず一番早く氷から開放され, 東面が標高が高いにもかかわらず一番新しいと判断された。 最後に, 解氷後の風化・侵食・堆積プロセスの作用とそれらによって作られる地形・地表状態について考察し表にまとめた。さらに, バルヒェン山やヌナタックではどのような地形・地表状態が分布するかを表にして, 相対的な新旧が比較できるようにした。 Landforms of Balchenfjella (Balchen Mountain) and nunataks near it in the Sør Rondane, East Antarctica, were described using a geomorphological map compiled from field work and aerial photographic interpretation for Balchenfjella and aerial photographic stereograms for major nunataks. While the nunataks are in general standing out above the general surrounding ice surfaces and many of them show landforms of alpine glacier origin, Balchenfjella is characterized by landforms of areal scouring owing to continental ice-sheet glaciation and most of the area still lies below the surrounding ice surface. In this regard, Balchenfjella is found to be very unique in the Sør Rondane. Distinctive demarcation lines between the surfaces of weathered materials and fresh bedrocks found at the eastern side of the several nunataks and Balchenfjella suggest a recent lowering of the ice-sheet surface by several tens of meters. Wide covers of weathered erratics and/or tills over Balchenfjella indicate that the mountain was once covered by ice tongues spilling and closing in from surrounding sides and ablation was very extensive there. Based on the spatial distribution of weathered materials, the relative deglaciation sequence was inferred for Balchenfjella, finding that the eastern part, although higher, was most recently deglaciated. Schematic sequences of ...